Production of Yerba Mate Extract with Zero Waste Principle Using Agricultural Recycling - Sousa, Aron Pinto de; Weinschutz, Regina; Motta, Antonio Carlos Vargas; Mathias, Alvaro Luiz (Revista Gestão & Sustentabilidade, 2024)
This study revealed that the yerba mate residue (YME) generated in producing Ilex paraguariensis tea extract is non-hazardous and non-inert. Reintroduced YME can make Mn, Fe and Zn available in yerba mate cultivation soil. A dose of YME (84.6, 56.4, 28.2, 14.1 t.ha-1 or not = control) was reintroduced into 5 recipient areas of the yerba mate forest in Paraná, Brazil to avoid unnecessary disposal from YME to landfill. The effect of reintroducing YME was evaluated in terms of soil change (potassium, phosphorus, sodium, calcium, magnesium, pH, and electrical conductivity) for two depths (0 to 10 cm or 10 to 20 cm), change in leaf composition, and growth of its branches for up to 210 days. YME agricultural recycling increased (p